ADHERENCE TO THE USE OF NEW ORAL ANTICOAGULANTS IN PATIENTS WITH ATRIAL FIBRILLATION – THE WAY TO SOLVE THE PROBLEM OF EFFICACY AND SAFETY OF TREATMENT - S. G. Kanorskii (Рациональная фармакотерапия в кардиологии)
Atrial fibrillation (AF) increases the risk of stroke,  therefore long-term anticoagulant therapy is the standard for the treatment of the absolute majority of patients with this arrhythmia. Variants of anticoagulant therapy include vitamin K antagonists, such as warfarin, whose  benefits are long established, but have a number of disadvantages, as well as their alternative – non-vitamin K antagonists – oral anticoagulants, recommended for the treatment of patients with AF with moderate or high risk of stroke. Adherence to pharmacotherapy is important for the long-term effectiveness of any medication; however, in the "real world" in patients with AF relatively low levels of adherence to drugs compared with clinical studies are expected. Experience in several areas of therapy, including the treatment of cardiovascular disease, shows that a low adherence to a constant intake of medications is common. However,  in this respect, simple dosing regimens may be beneficial, since long-term outcomes in AF are likely to depend on adherence to treatment. Rivaroxaban can be given in fixed doses without routine coagulation control, and phase III studies and actual clinical practice have demonstrated its safety and efficacy in patients with AF, including the elderly and patients with concomitant diseases. Taking an oral anticoagulant, not vitamin K antagonists, in particular rivaroxaban, once a day is potentially capable of improving adherence to therapy and the results of stroke prevention in patients with AF.